Yield and composition of milk from dairy cows fed diets containing cashew nuts - Pimentel, Patrícia; Reis, Ronaldo; Neiva, José Neuman; Coelho, Sandra; Pinto, Andréa (Revista Ciência Agronômica, 2017)
This work evaluated the production and composition of milk from dairy cows fed increasing levels of cashew nuts in the concentrate portion of the diet. Eight Holstein multiparous cows were used, between the third and fifth lactation, with an average milk yield of 28.0 ± 4.0 kg day-1, arranged in a double 4 x 4 Latin square experimental design. The assessed diets consisted of including different amounts of ground cashew nuts (CN): 0; 80; 160 and 240 g kg-1 of concentrate portion, which resulted in ether extract contents of 31.6; 46.0; 68.9 and 73.1 g kg-1 of dietary dry matter, respectively. Corn silage was used as the only roughage at a proportion of 50% and diets were formulated to be isoprotein. Diet was offered as a complete mixture. Average milk yield was 30.3 kg day-1. The concentration of protein, N-urea and lactose did not present significant variations (p>0.05) among the diets. The inclusion of 24% of cashew nut in the concentrate portion of the diet, maintains milk production, reduces milk fat content and together with the reduction in the concentration of short chain fatty acids and the increase in the concentrations of long chain fatty acids, provide a greater nutraceutical value to milk, making the use of cashew nut an excellent alternative for obtaining milk with more benefits to human health.